Characterization of miRNAs involved in response to poly(I:C) in porcine airway epithelial cells. (22nd November 2016) - Wang, L.; Wang, J. K.; Han, L. X.; Zhuo, J. S.; Du, X.; Liu, D.; Yang, X. Q.
Summary: MicroRNAs (miRNA) have been implicated in a variety of pathological conditions including infectious diseases. Knowledge of the miRNAs affected by poly(I:C), a synthetic analog of viral double‐stranded RNA, in porcine airway epithelial cells (PAECs) contributes to understanding the mechanisms of swine viral respiratory diseases, which bring enormous economic loss worldwide every year. In this study, we used high throughput sequencing to profile miRNA expression in PAECs treated with poly(I:C) as compared to the untreated control. This approach revealed 23 differentially expressed miRNAs (DEMs), five of which have not been implicated in viral infection before. Nineteen of the 23 miRNAs were down‐regulated including members of the miR‐17‐92 cluster, a well‐known polycistronic oncomir and extensively involved in viral infection in humans. Target genes of DEMs, predicted using bioinformatic methods and validated by luciferase reporter analysis on two representative DEMs, were significantly enriched in several pathways including transforming growth factor‐ β signaling. A large quantity of sequence variations (isomiRs) were found including a substitution at position 5, which was verified to redirect miRNAs to a new spectrum of targets by luciferase reporter assay together with bioinformatics analysis. Twelve novel porcine miRNAs conserved in other species were identified by homology analysis together with cloning verification. Furthermore, the expression analysis revealed the potential importance of three novel miRNAs in porcine immune response to viruses. Overall, our data contribute to clarifying the mechanisms underlying the host immune response against respiratory viruses in pigs, and enriches the repertoire of porcine miRNAs.